Adsorption behaviour of SF6 decomposed species onto Pd4-decorated single-walled CNT: a DFT study. (3rd July 2018) - Cui, Hao; Zhang, Xiaoxing; Zhang, Jun; Tang, Ju
ABSTRACT: Metal nanocluster decorated single-walled carbon nanotubes (SWCNT) with improved adsorption behaviour towards gaseous molecules compared with intrinsic ones, have been widely accepted as a workable media for gas interaction due to their strong catalysis. In this work, Pd4 cluster is determined as a catalytic centre to theoretically study the adsorption property of Pd4 -decorated SWCNT upon SF6 decomposed species. Results indicate that Pd4 -SWCNT possessing good responses and sensitivities towards three composed species of SF6 could realise selective detection for them according to the different conductivity changes resulting from the varying adsorption ability. The response of Pd4 -SWCNT upon three molecules in order is SOF2 > H2 S > SO2, and the conductivity of the proposed material is about to increase in SOF2 and H2 S systems, while declining in SO2 system. Such conclusions would be helpful for experimentalists to explore novel SWCNT-based sensors in evaluating the operating state of SF6 insulation devices. Abstract :